Technology of obtaining water-soluble surface-active substances by the method of phenol sulfomethylation - Nadiia Sokolenko (Eastern-European Journal of Enterprise Technologies, 2020)
The object of this study is a technology of the new surface-active substances (SAS) based on sulfomethylated phenol. The study's aim was to improve the technology by a catalytic method, implying the development of industrial schemes for the synthesis processes.